Real-time observation of ultrafast electron injection at graphene–Zn porphyrin interfaces. Issue 14 (9th March 2015) - Masih, Dilshad; Aly, Shawkat M.; Usman, Anwar; Alarousu, Erkki; Mohammed, Omar F.
Abstract : Femtosecond transient absorption spectra of zinc(ii ) porphyrin in the presence of graphene carboxylate (GC) reveal ultrafast electron transfer from the singlet excited ZnTMPyP* to GC, forming ZnTMPyP˙ + and GC˙ − radical ion pairs. Abstract : We report on the ultrafast interfacial electron transfer (ET) between zinc(ii ) porphyrin (ZnTMPyP) and negatively charged graphene carboxylate (GC) using state-of-the-art femtosecond laser spectroscopy with broadband capabilities. The steady-state interaction between GC and ZnTMPyP results in a red-shifted absorption spectrum, providing a clear indication for the binding affinity between ZnTMPyP and GC via electrostatic and π–π stacking interactions. Ultrafast transient absorption (TA) spectra in the absence and presence of three different GC concentrations reveal (i) the ultrafast formation of singlet excited ZnTMPyP*, which partially relaxes into a long-lived triplet state, and (ii) ET from the singlet excited ZnTMPyP* to GC, forming ZnTMPyP˙ + and GC˙ −, as indicated by a spectral feature at 650–750 nm, which is attributed to a ZnTMPyP radical cation resulting from the ET process.